2018
DOI: 10.2196/mhealth.9236
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Mobile Personalized Blood Glucose Prediction System for Patients With Gestational Diabetes Mellitus

Abstract: BackgroundPersonalized blood glucose (BG) prediction for diabetes patients is an important goal that is pursued by many researchers worldwide. Despite many proposals, only a few projects are dedicated to the development of complete recommender system infrastructures that incorporate BG prediction algorithms for diabetes patients. The development and implementation of such a system aided by mobile technology is of particular interest to patients with gestational diabetes mellitus (GDM), especially considering t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 32 publications
1
44
0
1
Order By: Relevance
“…The use of mobile health application system can promote the knowledge of self-monitoring of blood sugar, eating habits report, blood sugar control, and monitoring frequency and accuracy, so as to gradually improve patients' self-care ability. 24 In a previous study, a continuous application-based nursing approach significantly improved patients' overall self-care abilities. 25 It has also been reported that advantages of the application for continuous care include expansion of health education, provision of more options to the patient, and shortened intervals of intervention time between doctors and patients.…”
Section: Improved Self-managementmentioning
confidence: 87%
See 2 more Smart Citations
“…The use of mobile health application system can promote the knowledge of self-monitoring of blood sugar, eating habits report, blood sugar control, and monitoring frequency and accuracy, so as to gradually improve patients' self-care ability. 24 In a previous study, a continuous application-based nursing approach significantly improved patients' overall self-care abilities. 25 It has also been reported that advantages of the application for continuous care include expansion of health education, provision of more options to the patient, and shortened intervals of intervention time between doctors and patients.…”
Section: Improved Self-managementmentioning
confidence: 87%
“…As reported previously, with the improvement of self‐management ability, the accuracy of self‐monitoring of blood glucose, the self‐reporting of eating habits, and blood sugar control are gradually improved. The use of mobile health application system can promote the knowledge of self‐monitoring of blood sugar, eating habits report, blood sugar control, and monitoring frequency and accuracy, so as to gradually improve patients' self‐care ability . In a previous study, a continuous application‐based nursing approach significantly improved patients' overall self‐care abilities .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither of them assessed the effectiveness of PPGR prediction in GDM patients. We have developed a recommender system infrastructure that incorporates BG prediction models for GDM patients [13]. It is expected that integration of such models into an interactive mobile app will lead to the creation of personal recommendations for nutrition in real time to prevent hyperglycemia in patients with GDM.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed algorithms for predicting the following PPGR parameters: BG 60 min after the start of food intake (BG60), peak BG value after food intake (BGMax), area under the glycemic curve 1 (AUC60) and 2 h (AUC120) after the start of the meal and peak BG, and incremental area under the glycemic curve 2 h after food intake (iAUC120) [13]. The accuracy of predicting the AUC60 and AUC120 was adequate, but the model for predicting BG60 was not accurate enough.…”
Section: Introductionmentioning
confidence: 99%